Effect Of Fish Oil Alone or In Combination With Tomato Powder Supplementation In Feed On Egg Quality of Local Ducks - Faizal Andri; Eko Widodo; Osfar Sjofjan (Research Journal of Life Science, 2015)
The purpose of this research was to investigate the effect of fish oil alone or in combination with tomato powder supplementation in feed on egg quality of local ducks. Fivety 28-weeks old female local ducks with initial egg production of 4 days before research was 55.00 + 4.08% (coefficient of variation 7.42%) were randomly distributed to five treatments with 2 repetition and 5 birds of each. The treatmens were T0: basal feed (control); T1: basal feed + 1500 ppm fish oil ; T2: basal feed + 3000 ppm fish oil; T3: basal feed + 1500 ppm fish oil + 150 ppm tomato powder; T4: basal feed + 3000 ppm fish oil + 150 ppm tomato powder. Variable observed in this research were egg shape index, egg shell weight, yolk weight, and albumen weight. Data were analyzed using one-way Anova based on Completely Randomized Design, if significant effect appear was then continued with Duncan Multiple Range Test. The result showed that there were no significant effect (P>0.05) of fish oil alone or in combination with tomato powder supplementation in feed on egg shape index, egg shell weight, yolk weight, and albumen weight of local ducks. The conclusion of this research is that there was no effect of fish oil alone or in combination with tomato powder supplementation in feed on egg quality of local ducks.